The insular cortex-nucleus tractus solitarius glutamatergic pathway involved in acute stress-induced gastric mucosal damage in rats - Zepeng Wang; Xinyu Li; Yuanyuan Li; Xuehan Sun; Yuxue Wang; Tong Lu; Dongqin Zhao; Xiaoli Ma; Haiji Sun (Neurobiology of Stress)
Previous studies have shown that acute stress-induced gastric mucosal damage is linked to excessive activation of parasympathetic nervous system. The Insular Cortex (IC), the higher centers of the parasympathetic nervous system, serves as both the integration site of gastric sensory information and play a crucial role in the regulation of gastric function. However, whether the IC is involved in Restraint water-immersion stress (RWIS)-induced gastric mucosal damage has not been reported. In this study, we examined the expression of neuronal c-Fos, PSD95 and SYN-1 protein expression in IC during RWIS by immunofluorescence and western blot techniques, as well as assessed IC blood oxygenation level dependant (BOLD) through functional MRI. Chemical genetics techniques specifically modulate the activity of IC glutamatergic neurons and IC-nucleus tractus solitary (NTS) glutamatergic pathway to elucidate their contributions to RWIS-induced gastric mucosal damage. The results showed that the expression of c-Fos, PSD95, and SYN-1 protein in IC increased significantly after RWIS, along with a noticeable enhancement in fMRI signal intensity. Furthermore, inhibiting IC glutamatergic neurons and the IC-NTS glutamatergic neural pathway resulted in a significant reduction in gastric mucosal damage, an increase in the expression of Occludin, Claudin-1, and PCNA in the gastric wall, while the expression of nNOS decreased and CHAT increased. These findings suggest that during RWIS, IC glutaminergic neurons are activated, promoting stress-induced gastric mucosal damage through the IC-NTS-vagal nerve pathway.